Making the Psychological Dimension of Learning Visible: Using Technology-Based Assessment to Monitor Students’ Cognitive Development - Molnár, Gyöngyvér; Csapó, Benő (Frontiers in Psychology, 2019)
Technology-based assessment offers unique possibilities for collecting data about students’ cognitive development and using this data to provide students and teachers with feedback to improve learning. The aim of this study was to show how the psychological dimension of learning can be assessed in everyday educational practice through technology-based assessment in reading, mathematics and science. We analyzed three related aspects of the assessments: cognitive development, gender differences and vertical scaling. The sample for the study was drawn from primary school students in Grades 1–8 (aged 7 to 14) in Hungary. There were 1500 to 2000 students in each grade cohort. Online tests were constructed from 1638 items from the reading, mathematics and science domains in the eDia system. The results confirmed empirically that the disciplinary, application and psychological dimensions of learning can be empirically distinguished. Students’ cognitive development was the most steady (and effective) in mathematics where the greatest development happened in the first years of schooling. Path models suggested that the psychological dimension of learning can be predicted at a moderate level based on students’ level of school knowledge consisting of the disciplinary and application dimensions of learning as latent constructs. The predictive power was almost the same in both of the dimensions. Generally, girls developed faster in the psychological dimension of reading, mathematics and science learning; however, the size of gender differences varied by age and domain. This study (1) provides evidence that the psychological dimension of learning can be made visible even in an educational context and (2) highlights the importance of the explicit development of the psychological dimension of learning during school lessons, and (3) shows that there are gender differences in the developmental level of the psychological dimension of learning in favour of girls, but it varies by grade and domain.